Pemanfaatan E-Commerce dalam Peningkatan Penjualan pada Buger Sei Putih Kota Medan - Tengku Alvi Syahri Mahzura - (Jurnal Ekonomi Bisnis Manajemen Prima, 2020)
The purpose of this study is to determine the benefits of e-commerce in increasing sales of the Sei Putih Burger in Medan. Proxied e-commerce is a social media platform such as Instagram and blogs as well as marketplaces such as Grab food and Go food. The research method is descriptive qualitative, which describes respondents' answers and interview results which are then presented in tables and graphs using primary data sources and data collection techniques in the form of interviews, distributing questionnaires and observations. The results obtained show that the use of e-commerce in increasing sales is an increase in profits, increased partner relations, is known to the wider community, a better internal control system and better financial management ability to invest in assets such as gold and land. However, on the other hand there is a negative impact from the use of E-commerce in increasing sales, namely the cancellation of orders from customers, lack of technological knowledge in using EDC (Electronic Data Capture) machines, unavailability of large parking lots, network constraints on EDC machines and fictitious order opportunities.